2016
DOI: 10.3390/met6050097
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Wally, Z.J.; van Grunsven, W.; Claeyssens, F.; Goodall, R.; Reilly, G.C. Porous Titanium for Dental Implant Applications. Metals 2015, 5, 1902–1920.

Abstract: The authors wish to make the following corrections to the citations in the published paper [1].[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…[141] The authors concluded that small pores (about 188 mm) are more likely to promote cell differentiation at the beginning of the implant healing, whereas larger pores (313 μm and more) favor cell proliferation and bone ingrowth. [54] A porosity of 75-85%, as was described previously, is preferable for rapid bone ingrowth, according to Mour et al and a three-dimensional open porous structure is considered the most beneficial in the case of titanium implants. [54] A porosity of 75-85%, as was described previously, is preferable for rapid bone ingrowth, according to Mour et al and a three-dimensional open porous structure is considered the most beneficial in the case of titanium implants.…”
Section: Osseointegration Of Porous Implantsmentioning
confidence: 91%
“…[141] The authors concluded that small pores (about 188 mm) are more likely to promote cell differentiation at the beginning of the implant healing, whereas larger pores (313 μm and more) favor cell proliferation and bone ingrowth. [54] A porosity of 75-85%, as was described previously, is preferable for rapid bone ingrowth, according to Mour et al and a three-dimensional open porous structure is considered the most beneficial in the case of titanium implants. [54] A porosity of 75-85%, as was described previously, is preferable for rapid bone ingrowth, according to Mour et al and a three-dimensional open porous structure is considered the most beneficial in the case of titanium implants.…”
Section: Osseointegration Of Porous Implantsmentioning
confidence: 91%
“…Three different orientations of this same pore array were selected for investigation and are shown schematically in Figure 1. Using a Miller index notation these orientations are: 1) {100}compression normal to the {100} plane family (across the cubic cell) 2) {110}compression normal to the {110} plane family (along the short diagonal) 3) {111}compression normal to the {111} plane family (along the long diagonal)…”
Section: Sample Designmentioning
confidence: 99%
“…Cellular/porous titanium structures have attracted considerable research for use as structural biomaterials, due to the potential for tailoring their elastic properties to be closer to those of natural bone and the enhancement of osseointegration of the implant into the host. [1][2][3][4] The approach used in previous studies by the present authors has been to create cellular structures from Ti-6Al-4V alloy by additive manufacturing of a primitive cubic array of spherical pores. [5,6] In this way, the size of the pores and the inter-pore "gateways"both important parameters for osseointegrationare directly controlled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the potential applications open celled porous titanium is often suggested for use in biomedical implants into hard tissue, for example as reviewed for dental implants in [126] . The advantages for such applications come from the inherent inertness in the body of titanium, combined with the availability of pores for cells to grow into and provide better fixation and the ability of a porous structure to be designed with a particular Young's modulus, below that of the dense metal (for example by adjusting the level of porosity).…”
Section: Biomedical Implantsmentioning
confidence: 99%